Analisis Pengawasan Ketenagakerjaan Di Dinas Ketenagakerjaan Dan Transmigrasi Provinsi Bengkulu - Nova, Nova; Lorita, Evi; Saputra, Harius Eko (Professional: Jurnal Komunikasi dan Administrasi Publik, 2025)
This study aims to analyze the implementation of labor supervision carried out by the Manpower and Transmigration Office of Bengkulu Province. The research focuses on four key indicators based on the Regulation of the Minister of Manpower of the Republic of Indonesia Number 33 of 2016 Article 9 Paragraph (2), namely: labor coaching, inspection, testing, and criminal investigation. This study adopts a descriptive qualitative method using data collection techniques such as in-depth interviews, field observations, and documentation. Informants include two key informants and two supporting informants from the agency and company environment. The findings reveal that labor supervision in Bengkulu Province has been implemented according to established procedures and regulations. Labor inspectors conduct coaching through socialization and counseling, inspect compliance with labor norms, test occupational health and safety (OHS) systems, and investigate alleged violations of labor regulations. However, several challenges were identified, such as a limited number of inspectors and the complexity of violations in the field. This study contributes to strengthening the function of labor supervision at the regional level and serves as a reference for formulating more effective labor protection policies. Strengthening inspector capacity and improving cross-sectoral coordination are necessary to ensure more optimal supervision outcomes.